Modeling the customer satisfaction function: a two-country comparison - Ting, D.H. (Springer Verlag, 2018)
This paper provides a framework that integrates and reinterprets prior research on satisfaction modeling (function) and proposes the existence of non-linear and curvilinear/higher-order relationships to model online banking customers. It provides a framework that examines two closely related but distinct countriesâMalaysia, a developing country, and Singapore, a developed countryâand identifies whether modeling online banking customers through satisfaction is unique to each context or is generic. Using a systematic and step-by-step hierarchical moderated regression approach, this study tries to understand the relationship among repurchase intention, satisfaction, and trust, moderated by bank size. Malaysia portrays a linear relationship, while Singapore depicts non-linear and curvilinear/high-order relationships. The findings suggest that modeling online banking customers through satisfaction depends on a countryâs economic development. By contrast, prior studies on modeling customers through satisfaction were conducted independently and did not employ proper and systematic steps to capture the satisfaction function. Â© 2018, Institute of Applied Informatics at University of Leipzig.